Strategi Pengembangan UMKM Caldera Resto And Coffee Dengan Menggunakan Blue Ocean Strategy Dan Sistem Dinamik: Strategi Pengembangan UMKM Caldera Resto And Coffee Dengan Menggunakan Blue Ocean Strategy Dan Sistem Dinamik - Sonia Lumbanraja (Fakultas Teknik Universitas Ibnu Sina, 2024)
This study aims to design the right development strategy for MSMEs Caldera Resto and Coffee. The methods used are SWOT analysis, Blue Ocean Strategy, and System Dynamics. Data collection was conducted by distributing questionnaires to 100 respondents who visited Caldera Resto. The sampling technique used in the study is purposive sampling. The results showed that the development strategy designed greatly affect the increase in revenue at Caldera Resto and Coffee.